2012
DOI: 10.1371/journal.pone.0042261
|View full text |Cite|
|
Sign up to set email alerts
|

Age-Specific Sex-Related Differences in Infections: A Statistical Analysis of National Surveillance Data in Japan

Abstract: BackgroundTo prevent and control infectious diseases, it is important to understand how sex and age influence morbidity rates, but consistent clear descriptions of differences in the reported incidence of infectious diseases in terms of sex and age are sparse.Methods and FindingsData from the Japanese surveillance system for infectious diseases from 2000 to 2009 were used in the analysis of seven viral and four bacterial infectious diseases with relatively large impact on the Japanese community. The male-to-fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 41 publications
4
29
2
Order By: Relevance
“…Disease manifestations associated with viral infections often vary depending on the patient’s sex and age (Eshima et al, 2012). A previous study has reported that HHV-6 acquisition is more frequent in girls than boys (Zerr et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Disease manifestations associated with viral infections often vary depending on the patient’s sex and age (Eshima et al, 2012). A previous study has reported that HHV-6 acquisition is more frequent in girls than boys (Zerr et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…These data need to be confirmed by large prospective studies . Although an increased risk has been associated with the female gender, particularly for perioperative reactions, this gender pattern has not been documented among children (low) and the age/gender pattern for suspected DH is similar to the one for viral infections .…”
Section: Risk Factors and Differential Diagnosismentioning
confidence: 92%
“…A similar sex discrepancy in meningitis can be found in other countries [22,23]. The reasons for this may be the differences in the immune, endocrine and reproductive systems of males and females [24]. Almost all microbes that are pathogenic to human beings have a potential to cause meningitis, but a relatively small number of pathogens account for most cases, although the reasons for this association remain partly understood [25].…”
Section: Discussionmentioning
confidence: 67%